Project Scheduling in Complex Business Environments - Song, Wen (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Project scheduling is a common business management task. However, current business management environment has become more open and dynamic, which jeopardizes the effectiveness of the traditional approaches. In this abstract, I summarize my works in addressing two variations of project scheduling problems, including a combinatorial auction based approach for solving the decentralized multi-project scheduling problem, and a sampling based approach for solving the problem of project scheduling under time-dependent duration uncertainties.